Tillering response of liquid organic fertilizer and monosodium glutamate supplementation on Ganyong (Canna discolor Lindl.) - Mahdalina Mursilati; Agus Suprapto; Esna Dilli Novianto (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Ganyong (Canna discolor) is a plant that contains a high carbohydrate content, utilizing as alternative food for rice, especially in Indonesia. One of the factors affecting growth is the quantity of tillers, which affect the productivity of Ganyong's tuber. The purpose of this study was to discover the optimal combination of liquid organic fertilizer and monosodium glutamate to enhance the number of tillers. This study employed a randomized complete block design with a two-factor structure. The first factor to consider was the concentration of liquid organic fertilizer, which was specified as 0 ml/L, 2 ml/L, 3 ml/L, and 4 ml/L. The second factor was the monosodium glutamate dosage, which ranged from 0 to 3 g/plant, 6 g/plant, and 9 g/plant. Ganyong were cultivated for six months on farmland at an elevation of 460 m asl. Supplementation with liquid organic fertilizer resulted in a significant increase in the number of tillers. While monosodium glutamate supplementation had no significant effect on the formation of tillers. Combining liquid organic fertilizer at a concentration of 3 ml/L with monosodium glutamate 6 g/plant resulted in the optimal number of tillers.